2021
DOI: 10.1002/ecm.1472
|View full text |Cite
|
Sign up to set email alerts
|

Sea otter population collapse in southwest Alaska: assessing ecological covariates, consequences, and causal factors

Abstract: Sea otter (Enhydra lutris) populations in southwest Alaska declined substantially between about 1990 and the most recent set of surveys in 2015. Here we report changes in the distribution and abundance of sea otters, and covarying patterns in reproduction, mortality, body size and condition, diet and foraging behavior, food availability, health profiles, and exposure to environmental contaminants over this 25-yr period. The population decline, which resulted in densities on the order of 5% of environmental car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 135 publications
4
20
0
Order By: Relevance
“…Therefore, while wolf consumption of sea otters has enabled apparent competition and disruption of terrestrial food webs, the effects in the marine system are likely negligible indicating a donor-controlled shift in the recipient system ( 1 ). This example contrasts with orca predation in the Aleutians, which has changed the trajectory of the sea otter population ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, while wolf consumption of sea otters has enabled apparent competition and disruption of terrestrial food webs, the effects in the marine system are likely negligible indicating a donor-controlled shift in the recipient system ( 1 ). This example contrasts with orca predation in the Aleutians, which has changed the trajectory of the sea otter population ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wolves have been observed consuming sea otter carcasses and predating sea otter pups on the Alaska Peninsula ( 14 ), including one direct observation we made of three wolves ambushing a sea otter pup at a haul-out during summer 2021. Sea otters have occasionally been hunted on land by coyotes ( Canis latrans ) and brown bears ( Ursus arctos ), and by white sharks ( Carcharodon carcharias ) and orcas ( Orcinus orca ) at sea ( 44 , 45 ), but in this case, sea otters become the primary food source for a terrestrial predator.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al [6] identified a mortality-specific gene expression signature in ocean-tagged sockeye salmon (Oncorhynchus nerka), enabling predictions of spawning success. Tinker et al [7] included gene expression in an analysis of sea otter population collapse, offering substantive data supporting a controversial predation hypothesis. Broad-scale identification of gene expression patterns can provide mechanistic proxies of health [52].…”
Section: Discussionmentioning
confidence: 99%
“…The earliest observable signs of health impairment are altered levels of gene transcripts that are evident prior to clinical manifestation [3]. The amount of a particular gene that is transcribed is physiologically dictated by a number of intrinsic and extrinsic factors, including stimuli such as infectious agents, contaminant exposure, nutritional deficit, or trauma [4][5][6][7]. The use of novel molecular techniques may help identify these and other factors contributing to host susceptibility, which is critical to developing strategies to mitigate the effect of stressors on wildlife populations [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation